E.U. veterinary drug’s legislation - Cristina, T. Romeo (Medicamentul Veterinar, 2008)
The paper makes a short intoduction in veterinary drug’s legislation and presents de functioning mechanisms of European Medicines Agency(EMEA). There are presented EMEA’s structure, responsabilities, EU topicdefinitions and other specific aspects.